Modelling and Optimization of Combined Wastewater Treatment and CO2 Bio-fixation in a Batch Algal Photobioreactor - Al Ketife, Ahmed Majeed Daife (Curtin University, 2017)
The research focuses on investigation and optimization (using Box Behnken design) of the key parameters of CO2 gas concentration, light intensity, temperature, feedwater nutrient concentration, and wastewater origin (municipal primary and secondary, and petroleum industry) on photobioreactor algal growth parameters. A mathematical model is provided for predicting algal growth. Finally, the influence of light wavelength on algal growth is investigated. The outcomes can be used to inform design and operation of large-scale algal cultivation systems.